The Impact of Spirituality on Emotional Healing: A Qualitative Perspective - Moreau, Samuel; Bennett, Laura; Matthews, Brian (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to explore the impact of spirituality on emotional healing, examining how spiritual practices, beliefs, and social contexts contribute to individuals’ emotional recovery processes. Methods and Materials: A qualitative research design was employed, utilizing semi-structured interviews with 33 participants from Canada. Participants were selected based on their self-identified spiritual practices and experiences of emotional healing. Data were analyzed using NVivo software, and theoretical saturation was achieved through in-depth exploration of participants’ narratives. The study focused on identifying key themes related to the role of spirituality in emotional well-being. Findings: The study revealed five main themes: 1) Spiritual practices as coping mechanisms, including prayer, meditation, and scripture reading; 2) Transformation through spiritual insight, such as increased self-awareness and forgiveness; 3) Emotional healing in social-spiritual contexts, involving community support and shared testimonies; 4) Spiritual identity and emotional resilience, highlighting the role of a stable spiritual self in navigating emotional challenges; and 5) Challenges in spiritual healing, including spiritual doubt and conflicts with secular norms. Participants consistently reported that spiritual practices facilitated emotional regulation, provided meaning, and contributed to post-traumatic growth, while some also expressed difficulties with negative religious experiences. Conclusion: Spirituality plays a significant role in emotional healing, offering coping mechanisms, emotional resilience, and a transformative sense of purpose. However, its impact is complex, as negative spiritual experiences may also hinder emotional recovery. Practitioners should adopt a flexible, person-centered approach to integrating spirituality into emotional healing processes.